Aswaja Character Education Values and the Formation of Professional Ethics in Islamic Financial Institutions - millatur rofiah; Rizqia' Amalia; Ghufron Hamzah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2026)
Islamic Financial Institutions (IFIs) are not only required to comply with Sharia principles in a normative sense, but also to demonstrate professional ethics rooted in the moral consciousness of human resources. To date, efforts to strengthen professional ethics within IFIs have largely relied on regulatory and formal compliance approaches, which have not fully succeeded in cultivating internalized ethical integrity. This study aims to analyze the values of Ahlussunnah wal Jama’ah (Aswaja) character education and examine their relevance in shaping professional ethics within Islamic financial institutions. This research employs a literature based approach using a qualitative conceptual normative framework, drawing on classical and contemporary Aswaja literature, studies on Islamic professional ethics, and relevant documents related to Islamic financial institutions. Data were analyzed through content analysis and descriptive-analytical methods. The findings indicate that the core Aswaja values tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i‘tidal (justice and integrity) possess substantive relevance as foundational principles of professional ethics in IFIs, as they shape professional mindsets, attitudes, and behaviors in an integrated manner. The internalization of Aswaja values serves to bridge Sharia norms and modern business practices, enabling professional ethics to evolve beyond procedural compliance toward sustained moral awareness. This study emphasizes the strategic importance of integrating Aswaja based character education as a complementary approach to strengthening professional ethics in Islamic financial institutions. Keywords: Aswaja Character Education, Professional Ethics, Islamic Business Ethics, Islamic Financial Institutions.